Universo cultural carmelita no além-mar : formação e atuação dos carmelitas reformados nas capitanias do norte do estado do Brasil (sécs. XVI a XVIII) - André Cabral Honor (2013)
The thesis is based on the argument that the reformed Carmelites acted in the Portuguese America using a mixture of misticism and militancy, disregarding the observance. In order to comprehend this stand, the cultural universe of the Carmelites is analysed thoughtout its transposion to the Portuguese America by the friars of the Order of Our Lady of Mount Carmel who followed the Constitution of the Strict Observance, with emphasis on their daily life and works of art in their churches. Connecting documentation research in arquives to Panofsky‘s methodology of iconologic analysis, this research intends to interpret the role those reformed carmelite friars, also known as turonics, performed in the context of the Portuguese America as a means to understand the differences between the other members of the regular clergy and them. It follows the arrival of the first Carmelites to the Captaincy of Pernambuco in the sixteenth century and explores the insertion of the Turonic Reform in the convents of the northern captaincies of the State of Brazil, resulting in the creation of the Província Reformada de Pernambuco in 1720. Thus, by close-examining their performance throughout the eighteenth century it is possible to fathom how the aforesaid friars interacted and contributed to the establishment of the society that was developing in Brazil. This thesis integrates the Social History of Culture research line of the Doctorate‘s Degree Course in the History Graduate Program from Federal University of Minas Gerais.